Execução por quantia certa contra devedor insolvente - Pugliesi, Bárbara (2013)
Insolvency civil aims to ensure the main creditors of the debtor insolvent civil isonomic satisfaction of their claims. This purpose is manifested from the most remote historical origins, finding in the current legal position of outstanding importance. Many similarities can be registered between civil insolvency and bankruptcy of entrepreneurs and entrepreneurial companies, but there are also important distinctions that give the civil insolvency own identity within the legal world